Why do Public Blockchains Need Formal and Effective Internal Governance Mechanisms?. (June 2019) - YEUNG, Karen; GALINDO, David
Abstract : With the birth and rise of cryptocurrencies following the success of Bitcoin and the popularity of "Initial Coin Offerings", public awareness of blockchain technologies has substantially increased in recent years. Many blockchain advocates claim that these software artefacts enable radically new forms of decentralised governance by relying upon computational trust created via cryptographic proof, obviating the need for reliance on conventional trusted third-party intermediaries. But these claims rest on some key assumptions, which this paper subjects to critical examination. It asks: can existing mechanisms and procedures for collective decision-making of public blockchains (which we refer to as internal blockchain governance) live up to these ambitions? By drawing upon HLA Hart's Concept of Law, together with literature from regulatory governance studies, we argue that unless public blockchain systems establish formal and effective internal governance, they are unlikely to be taken up at scale as a tool for social coordination, and are thus likely to remain, at best, a marginal technology.